Implementation Plan in Response to the Board-Endorsed Recommendations for the IEO Evaluation of Recurring Issues from a Decade of Evaluation-Lessons for the IMF. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2015)
This paper sets out Management's response to the Independent Evaluation Office's (IEO) evaluation of Recurring Issues from a Decade of Evaluation: Lessons for the IMF.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet